The acquisition of aspect in Spanish by Chinese learners - Sun 孙玉良, Yuliang; González, Paz; Parafita Couto, Maria del Carmen; Mauder, Elisabeth; W. Child, Michael; Díaz, Lourdes; Taulé, Mariona (Círculo de Lingüística Aplicada a la Comunicación, 2019)
This work focuses on the acquisition of the pretérito indefinido and the pretérito imperfecto in Spanish by Chinese learners. Based on previous research, we predict that the differences in the aspectual systems of Mandarin Chinese and Spanish may prove challenging for Chinese learners in their use and comprehension of aspect in their inter-language. Moreover, we believe that the acquisition of aspect may not be synchronized at the morphological and semantic levels. By means of a grammatical task and a comprehension task, we found that the differences in the aspectual systems of the L1 and the L2 do cause difficulty for our learners. Additionally, our data support the claim that the acquisition of aspect at the morphological level occurs earlier than at semantic level.
Keywords: Acquisition of aspect in L2 Spanish; L1 Mandarin Chinese; acquisition of morphology; acquisition of semantic.